2023
DOI: 10.1002/nop2.1615
|View full text |Cite
|
Sign up to set email alerts
|

Opioid‐involved overdose trainings delivered using remote learning modalities

Abstract: Aim This education‐focused study examined changes in nursing students' knowledge and attitudes towards responding to opioid‐involved overdoses following participation in trainings delivered using remote learning modalities. Design This pre‐post study examined learning outcomes among 17 nursing students. Methods Participants completed the Opioid Overdose Attitude Scale and Opioid Overdose Knowledge Scale to assess attitudes and knowledge, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 22 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…One study reported a significantly higher number of naloxone prescriptions obtained by participants in the virtual group (42). For papers with other comparison groups, there was no significant differences in Kim et al, 2016 between reading-only and course groups, in Bergeria et al, 2019 for slide presentation and slide plus quiz groups, and in Giordano et al, 2023 between virtual reality video and videoconference groups (27,37,43). Huhn et al, 2018 showed the presentation-only group were more likely to complete the intervention compared to the group that received the same presentation coupled with a quiz, but there were no differences in knowledge and intervention acceptability (41).…”
Section: Comparison Between Different Modalities (N=12)mentioning
confidence: 97%
See 4 more Smart Citations
“…One study reported a significantly higher number of naloxone prescriptions obtained by participants in the virtual group (42). For papers with other comparison groups, there was no significant differences in Kim et al, 2016 between reading-only and course groups, in Bergeria et al, 2019 for slide presentation and slide plus quiz groups, and in Giordano et al, 2023 between virtual reality video and videoconference groups (27,37,43). Huhn et al, 2018 showed the presentation-only group were more likely to complete the intervention compared to the group that received the same presentation coupled with a quiz, but there were no differences in knowledge and intervention acceptability (41).…”
Section: Comparison Between Different Modalities (N=12)mentioning
confidence: 97%
“…One of these collected longitudinal data, and knowledge was not sustained at the three-month follow-up (31). Three of the video interventions reported on attitudes around opioid use disorder (OUD) or providing care during an opioid poisoning (25,36,37), with one of them reporting no change (36) and the other two reporting an increase in positive attitudes. All four studies that assessed overall satisfaction and/or qualitative feedback reported high satisfaction rates regarding the content, teaching methods, format, and/or mode of delivery of the intervention (23,25,31,51).…”
Section: Videos (N=9)mentioning
confidence: 99%
See 3 more Smart Citations